SIMPLE FINANCIAL CHECK-UP: DETECTING THE FINANCIAL HEALTH OF MSMEs IN THE SURABAYA SOUVENIR CENTER - Gusti Dian Prayogi; Rudiana Fibriani (Pedagogic Research-Applied Literacy Journal, 2025)
MSMEs still face challenges regarding low financial literacy and business financial management, particularly in independently detecting their financial health. This community service activity aims to improve the understanding and skills of MSME owners at the Surabaya Souvenir Center through the implementation of a simple financial check-up. The implementation methods included training, simulations, and direct mentoring using a participatory approach tailored to the partner's business conditions. The results showed an increase in the partners' understanding of business financial management, initial changes in cash flow recording practices, and the partners' ability to identify business liquidity conditions simply. Partner satisfaction surveys indicated an excellent level of satisfaction regarding the material, methods, and benefits of the activity. The discussion of the results confirms that a simple financial check-up is an effective, applicable, and relevant approach to improving the financial health of MSMEs and has the potential to be replicated in other MSME centers.